In the hindered rotation model we assumes constant bond angles $\theta$ and lengths $\ell$, with torsion angles between adjacent monomers being hindered by a potential $U(\phi_i)$. In Rubinstein's book problem 2.9 asks us to derive the Flory characteristic ratio for such a model, which is given as $C_\infty=\frac{1+\cos\theta}{1-\cos\theta}\cdot\frac{1+\langle\cos\phi\rangle}{1-\langle\cos\phi\rangle}$.

I am not sure where to start in working out the correlations between bonds to prove this relation. Starting from $\langle \vec{r_i}\cdot \vec{r_j}\rangle$ it seems from earlier derivations that I am expecting the correlations to be of the form

$\langle \vec{r_i}\cdot \vec{r_j}\rangle = \ell^2\left(\cos^{|i-j|}\theta + \langle \cos\phi\rangle^{|i-j|}\right)$, but I am having a hard time seeing how to show that. Any insights into how to see the correlations geometrically (or an indication that I am on the wrong track entirely) would be greatly appreciated.

Incidentally, it's a bit odd that there are no tags specifically for polymer physics.


1 Answer 1


The vector $\mathrm{r}_i$ is between the beads $i$ and $i+1$. Define a local coordinate system so that $x$ is along $\mathrm{r}_i$. The coordinate $y$ is defined so that $\mathrm{r}_{i-1}$, $\mathrm{r}_{i}$ are both on the same plane, and $z$ is normal to this plane. Thus we can write

\begin{align} \mathrm{r}_{i-1} &= (\ell\cos\theta, -\ell\sin\theta, 0)_i^T \\ \mathrm{r}_i &= (\ell, 0, 0)_i^T \\ \mathrm{r}_{i+1} &= (\ell\cos\theta, -\ell\sin\theta\cos\varphi_{i+1}, \ell\sin\theta\sin\varphi_{i+1})_i^T \end{align}

Or after working out the full coordinate transformation matrix from the above information, $$\begin{pmatrix}x \\ y \\ z \end{pmatrix}_i = A_i\begin{pmatrix}x' \\ y' \\ z' \end{pmatrix}_{i+1}$$ where $$A_i = \begin{pmatrix} \cos\theta & -\sin \theta & 0 \\ -\sin\theta\cos\varphi_{i+1} & -\cos\theta\cos\varphi_{i+1} & -\sin\varphi_{i+1} \\ \sin\theta\sin\varphi_{i+1} & \cos\theta\sin\varphi_{i+1} & -\cos\varphi_{i+1} \end{pmatrix}$$

Now \begin{align} \langle R^2 \rangle &= \left \langle \left(\sum_{i=1}^n \mathbf{r}_i\right) \cdot \left(\sum_{j=1}^n \mathbf{r}_j\right) \right\rangle = \sum_{i=1}^n \sum_{j=1}^n \langle \mathbf{r}_i \cdot \mathbf{r}_j\rangle \\ &= \sum_{i=1}^n \left( \sum_{j=1}^{i-1} \langle \mathbf{r}_i \cdot \mathbf{r}_j\rangle + \langle \| \mathbf{r}_i \|^2\rangle + \sum_{j=i+1}^{n} \langle \mathbf{r}_i \cdot \mathbf{r}_j\rangle \right) \\ &= n\ell^2 + 2\sum_{i=1}^n \sum_{j=i+1}^{n} \langle \mathbf{r}_i \cdot \mathbf{r}_j\rangle \end{align}

Using the transition matrix and noting that $j>i$, \begin{align} \langle \mathbf{r}_i \cdot \mathbf{r}_j\rangle &= \ell^2 \langle(1, 0, 0) A_i \cdots A_{j-1} (1, 0, 0)^T\rangle = \ell^2 \langle A_i \cdots A_{j-1}\rangle_{11} \\ &=\ell^2 (\langle A\rangle^{j-i})_{11} \end{align} Where $A$ is any of the matrices $A_i$, for example we could set $A = A_1$.

Thus $$\langle R^2 \rangle = n\ell^2 + 2\ell^2 \sum_{i=1}^n \sum_{j=i+1}^{n} (\langle A\rangle^{j-i})_{11} = n\ell^2 + 2\ell^2 \left(\sum_{i=1}^n (n-i) \langle A\rangle^{i}\right)_{11}$$

So towards the characteristic ratio: \begin{align} \frac{\langle R^2 \rangle}{n\ell^2} &= 1 + \frac{2}{n} \left(n\langle A\rangle(I-\langle A\rangle^{n})(I-\langle A\rangle)^{-1}\right. \\ & \qquad \left. - \langle A\rangle(I-(n+1)\langle A\rangle^{n} + n\langle A\rangle^{n+1})(I-\langle A\rangle)^{-2}\right)_{11} \\ & = \left((I+\langle A\rangle)(I-\langle A\rangle)^{-1} - \frac{2\langle A \rangle}{n}(I-\langle A\rangle^{n})(I-\langle A\rangle)^{-2}\right)_{11} \end{align}

Correlation between two beads tends to zero as distance goes to infinity, i.e. $\lim_{n\to\infty}\langle A\rangle^{n} = 0$, so $$C_\infty = \left((I+\langle A\rangle)(I-\langle A\rangle)^{-1}\right)_{11}$$

If the potential is symmetric, by the virtue of sine being odd $\langle \sin\varphi\rangle = 0$, and we have $$\langle A\rangle = \begin{pmatrix} \cos\theta & -\sin \theta & 0 \\ -\sin\theta\langle\cos\varphi\rangle & -\cos\theta\langle\cos\varphi\rangle & 0 \\ 0 & 0 & -\langle\cos\varphi\rangle \end{pmatrix}$$

Remembering that for a 3x3 matrix $T$ $$T^{-1} = \frac{1}{\det(T)}\begin{pmatrix}\det\begin{pmatrix} T_{22} & T_{23} \\ T_{32} & T_{33} \end{pmatrix} & \det\begin{pmatrix} T_{13} & T_{12} \\ T_{33} & T_{32} \end{pmatrix} & \det\begin{pmatrix} T_{12} & T_{13} \\ T_{22} & T_{23} \end{pmatrix} \\ \det\begin{pmatrix} T_{23} & T_{21} \\ T_{33} & T_{31} \end{pmatrix} & \det\begin{pmatrix} T_{11} & T_{13} \\ T_{31} & T_{33} \end{pmatrix} & \det\begin{pmatrix} T_{13} & T_{11} \\ T_{23} & T_{21} \end{pmatrix} \\ \det\begin{pmatrix} T_{21} & T_{22} \\ T_{31} & T_{32} \end{pmatrix} & \det\begin{pmatrix} T_{12} & T_{11} \\ T_{32} & T_{31} \end{pmatrix} & \det\begin{pmatrix} T_{11} & T_{12} \\ T_{21} & T_{22} \end{pmatrix} \end{pmatrix}$$ we have $$C_\infty = \frac{(1+\cos\theta)(1+\cos\theta\langle\cos\varphi\rangle) + \sin\theta \sin\theta\langle\cos\varphi\rangle}{(1-\cos\theta)(1+\cos\theta\langle\cos\varphi\rangle) - \sin\theta \sin\theta\langle\cos\varphi\rangle}$$

Which gives us the final relation $$C_\infty = \frac{(1+\cos\theta)(1+\langle\cos\varphi\rangle)}{(1-\cos\theta)(1-\langle\cos\varphi\rangle)}$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.